Chemistry Facts & Practice For A Level - "Parsonage, Max" (Oxford University Press N/A, 2001)
Oxford Facts and Practice' give facts and practice for A Level in 56 pages. Designed for the new A- and AS-Level specifications, each book starts with tips on exam technique and a description of the main specifications.